2020
DOI: 10.1186/s12889-020-08840-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the epidemiological impact on cervical cancer of switching from 4-valent to 9-valent HPV vaccine within a gender-neutral vaccination programme in Switzerland

Abstract: Background: An infection with high-risk human papillomavirus (HPV) is the obligatory aetiological factor for the development of cervical cancer. In Switzerland, the prevention strategy for cervical cancer is based on primary prevention via HPV vaccination and secondary prevention with an opportunistic screening programme for precancerous lesions. Vaccination is recommended to 11-26 years old male and female persons. The objective of the study was to assess the epidemiological impact on cervical cancer of switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
3
17
2
Order By: Relevance
“…14 The other genotypes identified in our population of Senegalese patients were HPV33, 35, 31 39, and 56, found at a low frequency of 0.3%-1.9% each, a range similar to that observed in other populations. 14 It is to underline that, in spite of the variations observed in prevalence for some genotypes, most of the HPV high-risk genotypes identified in our population are covered by the 9-valent HPV vaccine. In our case series of 207 cervical neoplasias cases, only two (0.96%) were related to viral genotypes not represented in the 9-valent vaccine, namely HPV39 and HPV56.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…14 The other genotypes identified in our population of Senegalese patients were HPV33, 35, 31 39, and 56, found at a low frequency of 0.3%-1.9% each, a range similar to that observed in other populations. 14 It is to underline that, in spite of the variations observed in prevalence for some genotypes, most of the HPV high-risk genotypes identified in our population are covered by the 9-valent HPV vaccine. In our case series of 207 cervical neoplasias cases, only two (0.96%) were related to viral genotypes not represented in the 9-valent vaccine, namely HPV39 and HPV56.…”
Section: Discussionsupporting
confidence: 86%
“…In our population of patients, the prevalence for HPV16/18 was 71.3%, a rate similar to that observed worldwide 14 . However, this rate is higher than the one reported by Ndiaye et al on ICC samples collected in Senegal and Mali from 2006 to 2010 despite a similar proportion of HPV positivity (85.9% vs. 86.8%) 20 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A study of the Swedish health registry found that from 2006–2017, the incidence of invasive cervical cancer was reduced by 88% for women receiving the quadrivalent HPV vaccine before the age of 17 and reduced by 53% in those vaccinated above 17 [ 27 ]. A prospective model in Switzerland found that the transition to the nine-valent HPV vaccine for 11–26 year old men and women would result in a further 24% reduction in cervical cancer incidence over the quadrivalent vaccine [ 28 ]. About 75.1% of US teens had received at least one dose of the HPV vaccine in 2020, which is projected to contribute to the continued decrease in cervical and head and neck cancer incidence [ 29 ].…”
Section: Cervical Cancermentioning
confidence: 99%
“…A previously validated and published HPV-type transmission dynamic model simulating the natural history of HPV infections and estimating the cost associated with HPV-related diseases in women has been extended to include all HPV-related diseases in both sexes (Elbasha et al, 2007;Elbasha & Dasbach, 2010;Boiron et al, 2016;Largeron et al, 2017;Mennini et al, 2017;Kind et al, 2020;Majed et al, 2021). HPV infection and disease state transitions, lifetime durations of infection-derived immunity, and unvaccinated compartments in this model have been described previously in detail (Elbasha et al, 2007).…”
Section: Designmentioning
confidence: 99%